PENGARUH STRES DAN KUALITAS KEHIDUPAN KERJA TERHADAP KEPUASAN KERJA DENGAN MOTIVASI SEBAGAI VARIABEL INTERVENING PADA PARA PNS TENAGA PERAWAT MEDIS RSUD KARDINAH (Students' Journal of Economic and Management, 2013)
RSUD Kardinah as public department service having accreditation of ISO always give attention satisfaction of employees activity which in this Medical Civil  Nurse case of RSUD Kardinah.This research is expected will be able to see efficacy of reduction stres hooked;correlated by quality of work life  to satisfaction through motivation as intervening variables The Method of this research used Linear Regretion Methode, wiyh result of that work stres having not negative motivation influence and also work satisfaction. Motivation having positive job satisfaction. Quality of work life having positive influence to motivation and also job satisfaction biger direct influence than undirect influence mediation by job motivation Keywords: significance, Job Stress, Quality of Worklife, Motivation and Job Satisfaction